Tingkat Ketepatan Kode Diagnosis Penyakit pada Rekam Medis di Rumah Sakit Elisabeth Medan - Agnes Jeane Zebua (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
The accuracy level of filling in the diagnosis code in the medical record document is very important because if the diagnosis code is not correct / not in accordance with ICD-10, it can cause a decrease in the quality of services in hospitals and affect data, report information, and the accuracy of the current INA-CBG's rates. used as a payment method for patient care. The purpose of this study was to analyze the accuracy of the disease diagnosis code at Elisabeth Hospital Medan. This type of research uses qualitative descriptive. Obtaining data from this study through interviews and observations. The results obtained from observations of medical recorders in hospitals. Based on the results of the study, it is known that from a total sample of 10 medical record documents at Elisabeth Hospital Medan, the accuracy of the disease diagnosis code has not reached 100%. The accuracy of the diagnosis code can be said to be very low because it only reaches 40% with the inaccuracy of the code reaching 60%. It is recommended for hospitals to increase their human resources by providing training to improve their competence and improve good communication with other medical personnel.